The derivatization of α-Pinena: Synthesis of Organonitrogen Compounds and Study of Its Potential as a Drug Candidate - Mohammad Farid Rahman; Rurini Retnowati; Suratmo Suratmo (Natural B, Journal of Health and Environmental Sciences, 2011)
a-Pinene is the major compound in oil of turpentine that can be developed as the- starting material to synthesize compounds that have potential as organonitrogen ingredients through biological and physiological properties. Changes a-pinene into organonitrogen compounds can be carried out via addition reactions to the alkene group through Ritter reaction using acetonitrile or benzonitrile reagent. Carbocation rearrangement that occurs in reaction to direct the reaction products varies. a-Pinene reaction with acetonitrile to produce the compounds N-[1-Methyl-1-(4-methyl-cyclohex-3-enyl)-ethyl]-acetamide, N-(1,5-Dimethyl-1-vinyl-hex-4-enyl)-acetamide and N-(2,6,6-trimethyl-bicyclo[3.1.1] hept-2-yl)-acetamide. While a-pinene reactions with benzonitrile to produce the compounds of N-(1,5-Dimethyl-1-vinyl-hex-4-enyl)-benzamide and N-[1-Methyl-1-(4-methyl-cyclohex-3-enyl)-ethyl]-benzamide. Reaction products with ingredients benzonitrile (LC50 = 203.86 ppm) has a higher toxicity than acetonitrile-based reaction product (LC50 = 504.80 ppm) based on the test Brine Shrimp Lethality Test (BSLT).